The Impact of Glycemic Control and Variability (HbA1c) on the Rate of Glomerular Filtration Rate Decline in Diabetes Mellitus: A Systematic Review - Cut Lisa Afrianna; Irmayani; T Iskandar Rizal (The International Journal of Medical Science and Health Research, 2025)
Introduction: Diabetic Kidney Disease (DKD) is a leading cause of end-stage renal disease (ESRD) globally. While mean glycated hemoglobin (HbA1c) is an established risk factor for DKD progression, the impact of long-term glycemic variability remains less clearly synthesized. This review systematically evaluates the association of both mean HbA1c and HbA1c variability with the rate of glomerular filtration rate (GFR) decline in individuals with type 1 (T1DM) and type 2 diabetes (T2DM). Methods: A systematic search of PubMed, Embase, Web of Science, and the Cochrane Library was conducted for longitudinal cohort studies published up to March 2024. Studies were included if they reported on mean HbA1c or long-term HbA1c variability (measured by standard deviation, coefficient of variation [CV], or variability score) and the primary outcome of GFR decline. The methodological quality of included studies was assessed using the Cochrane ROBINS-I tool for non-randomized studies. Results: A total of 16 longitudinal studies met the inclusion criteria. The findings consistently demonstrated that both higher mean HbA1c and greater HbA1c variability were significantly and independently associated with a more rapid decline in GFR. A "moderate-increasing" HbA1c trajectory was associated with a more than twofold increased risk of CKD progression (Hazard Ratio 2.23) (Critchley et al., 2019). High HbA1c variability, as measured by the highest versus lowest quartiles, was associated with an HR for renal function decline ranging from 1.26 to 1.47 across different metrics (Wang et al., 2024). Notably, this association persisted even in patients with well-controlled mean glycemia (HbA1c < 7.0%), where high variability still predicted a faster GFR decline (Tsai et al., 2020). Discussion: The evidence supports a "dual threat" model where both the absolute level and the instability of glycemia contribute to nephropathy progression. The independent role of HbA1c variability suggests that glycemic fluctuations may induce renal damage through distinct pathways, such as heightened oxidative stress and inflammation, beyond that of sustained hyperglycemia (Gorst et al., 2015). These findings underscore the need to look beyond a single HbA1c value and consider the entire glycemic trajectory in clinical risk assessment. Conclusion: Glycemic stability, in addition to achieving mean HbA1c targets, is a crucial therapeutic goal in diabetes management to preserve long-term renal function. Monitoring HbA1c variability may identify high-risk individuals who would otherwise be missed by conventional glycemic metrics.